Antibacterial Activity and Cytocompatibility of PLGA/CuO Hybrid Nanofiber Scaffolds Prepared by Electrospinning. (29th March 2015) - Haider, Adnan; Kwak, Sanghwa; Gupta, Kailash Chandra; Kang, Inn-Kyu
Abstract : The PLGA/CuO hybrid nanofibers scaffolds were prepared via electrospinning technique. The presence of CuO in the PLGA scaffolds was confirmed by transmission electron microscope (TEM) and X-ray photoelectron spectroscopy (XPS). The scaffolds were subjected to various antibacterial and cytobiocompatibility tests. The results not only showed excellent adhesion, proliferation, and viability (live/dead staining) for fibroblastic cells but also revealed that PLGA/CuO hybrid nanofiber scaffolds inhibited both Gram-positive and Gram-negative bacterial growth. The mechanism of the antibacterial activity was concluded to be based on the CuO nanoparticles and Cu ++ ions release. It is, therefore, evaluated that PLGA/CuO hybrid nanofiber scaffolds can be a useful candidate for wound dressing.